Influence of CeO2 addition on Si3N4 ceramics. (April 2015) - Li, Y. X.; Han, W. B.; Chen, G. Q.; An, J. D.
<x content-type="archive" xml:space="preserve">Abstract</x> Dense β-Si3N4 ceramics were fabricated by hot-pressed sintering at 1800°C with a mixture of α-Si3N4 powders and different amount of CeO2 additive, of which the latter is less frequently used as sintering aid to Si3N4. The effects of sintering additives concentration on grain boundary phase composition, phase transformation and the grain size of silicon nitride ceramics were investigated, followed by the influences of sintering additives content on the densification and mechanical properties of silicon nitride ceramics. The results show that increased CeO2 addition leads to greater growth anisotropy of elongated grains, and the effects of the microstructure on fracture toughness of silicon nitride ceramics were closely related to CeO2.